The Regional Head Elections (Pilkada) 2020 During Covid-19 Pandemic: A Projection - Hizra Marisa; Ade Pornauli; Achmad Indra; Alya Aurora (JOELS: Journal of Election and Leadership, 2020)
This study aims to find out a projection and how the development of elections during COVID-19 pandemic. The regional heads elections is one manifestation of the reform movement in 1998 which wants a change in state administration after being dominated by authoritarianism to become democratic. This election is known to the public as a venue for the election of regional heads who will serve or lead. Covid-19 pandemic is a virus transmission and causes an outbreak ove the world including Indonesia. A number of regions contributed to the 2020 elections. The regional head election system in 2020 is the third time held in Indonesia. The ballot is planned to be held simultaneously on September 2020. The total area that will carry out simultaneous regional head elections in 2020 is 270 regions with 9 provinces, 224 districts and 37 cities. The government regulation in lieu of law number 2/2020 on the local election was finally set by President Joko Widodopada on May 4th, 2020. The election which originally took place on September 23rd was finally postponed for 3 months, which became on December 2020. This step was criticized because it was considered ignoring COVID-19 pandemic.